PEMBELAJARAN MATEMATIKA DENGAN MENGGUNAKAN MODEL KOOPERATIF TIPE TALKING STICK - Amir, Almira (IAIN PADANGSIDIMPUAN, 2016)
Learning math is a process or activity of teachers in teaching mathematics to students, to create the ability, potential, interests, diverserse talents so that the interaction optimal airning at obtaining a variety of learning experiences better and meaningful. A teacher should be able to apply innovative instructional strategies that can improve the spirit of the students in learning, so students will not feel bored with the materialÂ that has been taught so as to achieve maximum learning results.Cooperative learning model talking stick is an interesting mathematical model of learning and makes students more axcited and interested in learning so that student learning outcomes for the better. Students become more active in presenting their opinions and respond to his opinion. In addition, with the stick rolling with the accompaniment of music, then learning of mathematics more fun.